Studi Tentang Kemiskinan di Kabupaten Batanghari dan Kabupaten Muaro Jambi Periode 2002-2016 - Nasution, Deyra Qatrunnada; Yulmardi, Yulmardi; Hardiani, Hardiani (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2017)
The purpose of this study was to determine the development of poverty levels in Batanghari and Muaro Jambi regencies, to know the development of depth index and poverty severity index in Batanghari and Muaro Jambi District and find out the differences in poverty levels, depth index and poverty severity index between Batanghari and Muaro Jambi districts . This study uses time series research methods with quantitative analysis tools for different tests (t-test) using Independent Sample T-test. The data used in this research is secondary data. Secondary data comes from the Central Statistics Agency of Jambi Province. The results of this study indicate that during the period 2002-2016 the average poverty level in Batanghari District was 13.37% and the average poverty rate in Muaro Jambi District was 6.51%. Based on the results of independent sample t-test, it was found that each independent variable, namely poverty level, poverty depth index, and poverty severity index in Batanghari District together had significant differences to poverty level, poverty depth index, and poverty severity index. in Muaro Jambi District for the period 2002-2016.